2017
DOI: 10.1093/pm/pnx058
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and Opioid System Interactions in Exercise-Induced Hypoalgesia

Abstract: As reductions in pain (i.e., EIH) were observed following both conditions, these results suggest that the opioid system may not be the primary system involved in exercise-induced hypoalgesia and that 2-AG and 2-OG could contribute to nonopioid exercise-induced hypoalgesia. Moreover, as exercise-induced increases in AEA and OEA were blocked by naltrexone pretreatment, this suggests that the opioid system may be involved in the increase of AEA and OEA following exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 26 publications
1
64
1
1
Order By: Relevance
“…Studies have also shown that intense exercise is followed by an increase in heat-pain thresholds, a phenomenon termed "exercise induced analgesia" (EIA; Scheef et al, 2012;Koltyn, Brellenthin, Cook, Sehgal, & Hillard, 2014;Crombie, Brellenthin, Hillard, & Koltyn, 2017). Although EIA lasts up to 30 min (Hoffman et al, 2004), perhaps its effects are cumulative, namely the EIA of athletes is constantly on an "on" mode, whereas it has an "on" and "off" modes among non-athletes, depending on the frequency/intensity of their exercises.…”
Section: Basal Pain Perception Of Athletesmentioning
confidence: 99%
“…Studies have also shown that intense exercise is followed by an increase in heat-pain thresholds, a phenomenon termed "exercise induced analgesia" (EIA; Scheef et al, 2012;Koltyn, Brellenthin, Cook, Sehgal, & Hillard, 2014;Crombie, Brellenthin, Hillard, & Koltyn, 2017). Although EIA lasts up to 30 min (Hoffman et al, 2004), perhaps its effects are cumulative, namely the EIA of athletes is constantly on an "on" mode, whereas it has an "on" and "off" modes among non-athletes, depending on the frequency/intensity of their exercises.…”
Section: Basal Pain Perception Of Athletesmentioning
confidence: 99%
“…The key mechanisms in exercise-induced hypoalgesia may include opioid and non-opioid systems (e.g. the endocannabinoid system) 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This is known to evoke Type IV (C-fiber) temporal pain summation. The same group also focussed on molecular parameters of pain, especially the involvement of endocannabinoid markers 10,25 . Furthermore, conditioned pain modulation has been proposed to examine central pain inhibitory processing 26 .…”
Section: Discussionmentioning
confidence: 99%